Building certification methods and a proposed new method: Bioharmological conformity assessment - Ekinci, Cevdet Emin (Gazi Univ, Fac Engineering Architecture, 2024)
In this study, the theoretical bases of the building certification systems that are being applied around the world and the Bioharmological Conformity Assessment system, which is a new certification system, are explained (Table A). Systems/methods based on life cycle assessment, criteria-based evaluation and building performance based evaluation are used in the measurement and certification of buildings. In this study, the theoretical principles of a new method developed and proposed according to the user identity and intended use of the building are explained. The name of this method is bioharmological conformity assessment methods. Its short name is BCA. The BCA method can be applied to all buildings for residential, educational, health, administrative and commercial use. Evaluation of buildings is made under four main headings. These are the building's engineering features and architectural features. With these features, it differs from other systems and/or methods used in the international arena. For example, the engineering features of the buildings are presented in 12 sub-headings and with at least 600 questions, the current conditions of the buildings are revealed, inadequacies and deficiencies are determined, and the issues that need to be done in terms of the user identity and purpose of use of the building are put forward in order of priority. It has been observed that an important part of these systems are sustainable and green building features. The features of a new system as an alternative to the existing methods and the principles regarding the application steps are given. An explanatory sample application is included in the text in order to assist the parties who are doing or will be doing certification studies.
Bina sertifikalandırma yöntemleri ve önerilen yeni bir yöntem: Biyoharmolojik uygunluk değerlendirme
Keywords: Bioharmology; Green buildings; Bioharmological buildings; LEED; BREEAM